Increasing Brand Awareness through Digital Marketing and Digital Transformation: A Literature Review - Sugiat, Jajang (PT Inovasi Pratama Internasional, 2025)
In the rapidly evolving digital era, companies are faced with the challenge of utilizing digital technology to increase brand awareness. Digital marketing and digital transformation have become major factors in strengthening brand awareness and creating a more personalized consumer experience. This study aims to analyze the relationship between digital marketing, digital transformation, and brand awareness in various industries. The type of research used is descriptive research with a quantitative approach. The population in this study were companies that have implemented digital marketing, with purposive sampling techniques and a sample size of 150 companies. The research locations were various companies in Indonesia that use digital channels in their marketing. The results showed that an integrated digital marketing strategy and the utilization of digital technologies such as artificial intelligence (AI) and big data analytics play an important role in increasing brand awareness. Consistency of brand messages and the use of the right channels greatly influence the success of marketing campaigns in building brand awareness. This research provides important implications for companies in designing and implementing more effective digital marketing strategies and utilizing digital technology to increase loyalty and brand awareness in a sustainable manner.